Molecular dynamics simulations of apo and holo forms of fatty acid binding protein 5 and cellular retinoic acid binding protein II reveal highly mobile protein, retinoic acid ligand, and water molecules. Issue 7 (19th May 2018) - Hunter, Nathanael H.; Bakula, Blair C.; Bruce, Chrystal D.
Abstract : Structural and dynamic properties from a series of 300 ns molecular dynamics, MD, simulations of two intracellular lipid binding proteins, iLBPs, (Fatty Acid Binding Protein 5, FABP5, and Cellular Retinoic Acid Binding Protein II, CRABP-II) in both the apo form and when bound with retinoic acid reveal a high degree of protein and ligand flexibility. The ratio of FABP5 to CRABP-II in a cell may determine whether it undergoes natural apoptosis or unrestricted cell growth in the presence of retinoic acid. As a result, FABP5 is a promising target for cancer therapy. The MD simulations presented here reveal distinct differences in the two proteins and provide insight into the binding mechanism. CRABP-II is a much larger, more flexible protein that closes upon ligand binding, where FABP5 transitions to an open state in the holo form. The traditional understanding obtained from crystal structures of the gap between two β-sheets of the β-barrel common to iLBPs and the α-helix cap that forms the portal to the binding pocket is insufficient for describing protein conformation (open vs. closed) or ligand entry and exit. When the high degree of mobility between multiple conformations of both the ligand and protein are examined via MD simulation, a new mode of ligand motion that improves understanding of binding dynamics is revealed.